2006
DOI: 10.1160/th06-05-0267
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thromboembolic events among 8,860 patients with thalassaemia major and intermedia in the Mediterranean area and Iran

Abstract: SummaryBeta-thalassaemia isa congenital haemolytic anaemia characterized by partial (intermedia, TI) or complete (major, TM) deficiency in the production of β-globin chains.The primary aim of this study was to determine the prevalence of thromboembolic events in patients with β-thalassaemia.To achieve this,a multiple-choice questionnaire was sent to 56 tertiary referral centres in eight countries (Lebanon, Italy, Israel, Greece, Egypt, Jordan, Saudi Arabia and Iran), requesting specific information on patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
300
3
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(323 citation statements)
references
References 18 publications
6
300
3
14
Order By: Relevance
“…12 Circulating MP can be very noxious in different clinical settings such as acute coronary syndromes, atherosclerosis, post-transfusional acute respiratory distress syndrome, diabetes mellitus, systemic inflammatory disease and disseminated intravascular coagulation. 10,12,36,39,40 MP originating from RBC membranes have also been considered a major cause of premature atherosclerosis described in TI patients. 13 The mechanisms responsible for the generation of MP appear very complex in different cell types 32 and very little is known about thalassemic RBC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Circulating MP can be very noxious in different clinical settings such as acute coronary syndromes, atherosclerosis, post-transfusional acute respiratory distress syndrome, diabetes mellitus, systemic inflammatory disease and disseminated intravascular coagulation. 10,12,36,39,40 MP originating from RBC membranes have also been considered a major cause of premature atherosclerosis described in TI patients. 13 The mechanisms responsible for the generation of MP appear very complex in different cell types 32 and very little is known about thalassemic RBC.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of almost all complications are significantly higher in splenectomized patients than in nonsplenectomized patients. 36 The development of these complications has been attributed to the presence of high platelet counts and/or to an increased number of pathological RBC with potentially thrombogenic, negatively charged membranes. Thrombin generation is significantly higher in splenectomized TI patients than in control subjects or patients who have not undergone splenectomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published multinational study of 8,860 thalassaemia patients from the Mediterranean region and Iran showed that thromboembolic events were 4.38 times more frequent in TI than in TM, and were particularly prevalent in splenectomized patients and patients with profound anaemia (hemoglobin level <9 g/dL). 41 Ischemic strokes have also been observed in combination with cardiac valvular lesions resulting from elastic tissue defect and/or atrial fibrillation. 29 However, thrombosis may be a sub-clinical process and may remain undetected.…”
Section: 37mentioning
confidence: 99%
“…1 In addition to increased thrombin and fibrin generation, increased tissue factor activity, and increased platelet activation (Figure 1), patients with hemolytic anemias manifest thrombotic complications, including venous thromboembolism, in situ pulmonary thrombosis and stroke. [1][2][3][4][5][6][7] Furthermore, the risk of thromboembolic complications appears to be higher following splenectomy. 1,3,6 The mechanism of coagulation activation in hemolytic anemias is likely multifactorial.…”
mentioning
confidence: 99%